2019
DOI: 10.1080/14992027.2018.1531154
|View full text |Cite
|
Sign up to set email alerts
|

What do hearing healthcare professionals do to promote hearing aid use and benefit among adults? A systematic review

Abstract: Objective: To conduct a systematic review of the evidence in relation to what hearing healthcare professionals do during hearing aid consultations and identifying which behaviours promote hearing aid use and benefit among adult patients. Design: Searches were performed in electronic databases MEDLINE, EMBASE, CINAHL, PsycInfo, Web of Science, PubMed and Google Scholar. The Crowe Critical Appraisal Tool and Melnyk Levels of Evidence were used to assess quality and level of evidence of eligible studies. Behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(132 reference statements)
1
4
0
Order By: Relevance
“…However, based on our video observations of clinical interactions in the Standard Care group, none of the information about social and environmental consequences as stated in the I-PLAN materials was delivered by the study audiologists. The video observations of the study audiologists were also in line with a systematic review which concluded that audiologists typically focus on provision of information concerning technical aspects of hearing aids during hearing aid consultations (Ismail et al, 2019).…”
Section: Effects Of the I-plan Interventionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, based on our video observations of clinical interactions in the Standard Care group, none of the information about social and environmental consequences as stated in the I-PLAN materials was delivered by the study audiologists. The video observations of the study audiologists were also in line with a systematic review which concluded that audiologists typically focus on provision of information concerning technical aspects of hearing aids during hearing aid consultations (Ismail et al, 2019).…”
Section: Effects Of the I-plan Interventionsupporting
confidence: 59%
“…This suggests that interventions should target “volitional processes” (e.g., action planning) to increase hearing aid use among adult patients ( Sawyer et al., 2019 ). In addition, given that little is known about what behaviors audiologists perform that may facilitate hearing aid use, studies that involve audiologists delivering interventions face-to-face are needed to provide an evidence base for clinical practice ( Ismail et al., 2019 ).…”
mentioning
confidence: 99%
“…Wilson and Stephens also noted that users' attitudes toward hearing-aids impacted both HA use and satisfaction. Ismail et al's 31 review on hearing providers current practice suggested that perhaps the lack of improvement in HA use and other outcomes is due to ineffective audiological consultations. Their review identified that hearing-aid provider behaviors and strategies had not changed, despite patient concerns and published knowledge of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…As the CCAT does not include an explanation of the percentages obtained, the quality of the included studies was classified as poor (score: 0-50%), moderate (score: 51-74%), and high (score: 75-100%), based on criteria used in previous studies. [38][39][40]…”
Section: Quality Assessmentmentioning
confidence: 99%